ANALYSIS OF THE INFLUENCE OF POPULATION NUMBER AND EMPLOYMENT OPPORTUNITIES ON POVERTY IN THE CITY OF PALANGKARAYA - Harati, Rima (PT. Altin Riset Publishing, 2025)
This research aims to analyze the influence of population and employment opportunities that occurred during 2010-2024 on poverty in Palangkaraya City. This research is descriptive quantitative and uses multiple regression analysis tools. The results of multiple regression analysis using SPSS 25 show that population and employment opportunities do not have a significant influence on poverty in the city of Palangkaraya. Meanwhile, based on classical assumptions, it is explained that the regression model in this study meets the normality assumption, multicollinearity occurs in the regression model in this study, in this regression model symptoms of heteroscedasticity occur, it is concluded that there are no symptoms of autocorrelation.